COMPARATIVE EVALUATION OF TREATMENT METHODS FOR VARROTOSIS IN HONEY BEES - M. Umitzhanov; N. Akimzhan; D. Khussainov; A. Zhylkaidar; A. Aliyev; G. Akhmetova; S. Usmangalieva; G. Omarbekova; A. Arysbekova; B. Kanatov; Y. Moldakhanov; S. Bayantasova; et al. (Animal Health and Biosafety, 2026)
Beekeeping is not only a fascinating hobby but also a profitable business. However, it requires knowledge and skills to ensure the health of bees and the quality of the product. One of the main problems in modern beekeeping is the Varroa mite, which carries diseases and can lead to the death of a bee colony. The Varroa mite causes a number of bee diseases because it harbors pathogens that cause various infections. These diseases lead to decreased bee productivity, deterioration in honey and wax quality, and the death of bee colonies. Furthermore, the Varroa mite facilitates the spread of other pathogens, such as bacteria, viruses, and fungi. Thus, the Varroa mite is a serious problem for beekeepers, requiring effective control and prevention measures. To this day, various methods exist for treating honey bees for Varro. Each method differs from the other and has its own advantages and disadvantages when used to treat bee colonies. In our experiment, when treating honey bees, we used an “Aerosol Creator” which used a vapor of anthracic acid in certain dosages depending on the strength of the bee colonies (Umitzhanov M., et al., 2005). In the summer, the device was used in production conditions to treat 80 bee colonies affected by varroatosis in honey bees in the Talgar district, Bereke village, and Soldatskoye Gorge site in the Almaty region. While examining the bee colonies, we discovered that their strength varied. We found weak and average colonies infested with Varroa Jacobsoni mites. Three doses of a therapeutic formic acid aerosol were applied to each colony using a rubber pump. During an inspection at the end of the summer, we found no Varroa Jacobsoni mites in the bee colonies. The colonies' development returned to normal, and the number of honeybees increased. This was evident in the collection and sealing of honey, bee bread, and the number of honeycomb frames filled with bees. The proposed device for generating aerosols allows for the dosed treatment of varroatosis in bees using formic acid vapors, which is simple, ensures operator safety, and increases the cost-effectiveness of treating bee diseases.